IDENTIFIKASI PENGGUNAAN LAHAN DI KECAMATAN KALAWAT DENGAN MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS KABUPATEN MINAHASA UTARA - Vikni Yopy Maki; DR. Ir. Sandra E. Pakasi, MSi.; Ir. Maria Montolalu, MP. (Universitas Sam Ratulangi, 2017)
ABSTRACTVikni Yopy Maki. 120318032. Identification the Landuse in Kalawat, North Minahasa Regenci Using Geographic Information System Supervised by Dr.Ir. Sandra E. Pakasi, MSi and Ir. Maria Montolalu, MP.This study aims to determine the landuse in the District of Kalawat, North Minahasa Regency using Geographic Information System(GIS). The research has been conducted since October to December 2016 in Kalawat North Minahasa Regency. This research uses descriptive method consisting of field survey and overlay map. The results shows that GIS has the ability to connect various data at a certain point on earth, combine, analyze and mapping. The data to be processed in the GIS is spatial data whichis geographically oriented data that has a certain coordinate system, as reference data. There are seven types of landuse in Kalawat such as: roads, settlements, coconut plantations, mixed plantations, irrigated sawahs, fishponds and rivers. The total area of Kalawat is 3819.79 ha, which consist of Mixed plantation 3027,27 ha (79,25%), settlement 410,08 ha (10,74%), coconut plantation 239,59 ha (6,27%), irrigated rice fields 126.62 ha (3.32%) and fish farm 16,23 ha (0,42%). Kalawat has road wits length 218,72 km and length of river 35,37 km.